(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Depending on the meteorological observations which obtained from the meteorological organization and seismology in Baghdad observation at city of Hilla and during the duration (1981-2015). The relationship between dust storms and some of weather elements such as temperature has been investigated, wind speed, and relative humidity as well as their impacts on occurrence of dust storms. It was found that each of temperature and wind speed have a positive correlation with occurrence of dust storms with positive correlation coefficient (r = 0.3). While the relative humidity has a negative correlation with dust storms and the correlation coefficient has the value (r = -0.29). Additionally it was studied the relationship between the correlation of dust storms and yearly intervals over the period (1981- 2015). It was noted that the occurrence of dust storms has a negative correlation during this duration, on the other hand the highest value of the dust storms was recorded during (1987) .